How to Become a Uropathogen: Comparative Genomic Analysis of Extraintestinal Pathogenic Escherichia coli Strains - Brzuszkiewicz, Elzbieta; Brüggemann, Holger; Liesegang, Heiko; Emmerth, Melanie; Ölschläger, Tobias; Nagy, Gábor; Albermann, Kaj; Wagner, Christian; Buchrieser, Carmen; Emődy, Levente; Gottschalk, Gerhard; Hacker, Jörg; et al. (Proceedings of the National Academy of Sciences - PNAS, 2006)
Uropathogenic Escherichia coli (UPEC) strain 536 (O6:K15:H31) is one of the model organisms of extraintestinal pathogenic E. coli (ExPEC). To analyze this strain's genetic basis of urovirulence, we sequenced the entire genome and compared the data with the genome sequence of UPEC strain CFTO73 (O6:K2:H1) and to the available genomes of nonpathogenic E. coli strain MG1655 (K-12) and enterohemorrhagic E. coli. The genome of strain 536 is ≈292 kb smaller than that of strain CFTO73. Genomic differences between both UPEC are mainly restricted to large pathogenicity islands, parts of which are unique to strain 536 or CFTO73. Genome comparison underlines that repeated insertions and deletions in certain parts of the genome contribute to genome evolution. Furthermore, 427 and 432 genes are only present in strain 536 or in both UPEC, respectively. The majority of the latter genes is encoded within smaller horizontally acquired DNA regions scattered all over the genome. Several of these genes are involved in increasing the pathogens' fitness and adaptability. Analysis of virulence-associated traits expressed in the two UPEC 06 strains, together with genome comparison, demonstrate the marked genetic and phenotypic variability among UPEC. The ability to accumulate and express a variety of virulence-associated genes distinguishes ExPEC from many commensals and forms the basis for the individual virulence potential of ExPEC. Accordingly, instead of a common virulence mechanism, different ways exist among ExPEC to cause disease.